2003
DOI: 10.14214/sf.481
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between empty seed and genetic factors in European beech (Fagus sylvatica L.)

Abstract: The relationship between percentage of empty seed (Pes) and genetic factors was explored in an isolated stand of European beech (Fagus sylvatica L.). Nine allozyme loci (GOT-B, IDH-A, LAP-A, MDH-B, MDH-C, MNR-A, 6-PGDH-A, PGI-B and PGM-A) were used to estimate genetic factors. Pes ranged from 4.8% to 40.9% for seed samples of 91 trees within the stand and showed an approximate normal distribution. The average Pes was 21.4% and the repeatability of Pes was 43.4%. The multilocus estimate for outcrossing rate (t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Seed mass was also significantly correlated with the mean germination rate per population in B. pendula in northern Sweden (Holm 1994). A low seed weight may result from the lack of an ovule because birches produce fruits even in the absence of pollination (Atkinson 1992), and in many angiosperm species, empty seeds can also be an effect of self-incompatibility or inbreeding (Wang 2003). Birches are generally recognized as self-incompatible plants (Atkinson 1992) because self-fertilization tests conducted with 31 trees belonging to nine species produced a relatively high proportion of viable seeds only in B. papyrifera and B. alleghaniensis (Clausen 1966).…”
Section: Discussionmentioning
confidence: 99%
“…Seed mass was also significantly correlated with the mean germination rate per population in B. pendula in northern Sweden (Holm 1994). A low seed weight may result from the lack of an ovule because birches produce fruits even in the absence of pollination (Atkinson 1992), and in many angiosperm species, empty seeds can also be an effect of self-incompatibility or inbreeding (Wang 2003). Birches are generally recognized as self-incompatible plants (Atkinson 1992) because self-fertilization tests conducted with 31 trees belonging to nine species produced a relatively high proportion of viable seeds only in B. papyrifera and B. alleghaniensis (Clausen 1966).…”
Section: Discussionmentioning
confidence: 99%
“…Small population size and severe isolation of the population may increase pollen shortage through the associated scarcity of potential pollen parents and pollen immigration from outside populations. Wang (2003) found that the proportion of empty seeds was significantly negatively correlated with outcrossing rates in F. sylvatica, and pollen limitation generally increases selfing rates of plant species (Larson and Barrett 2000). Thus, pollen limitation-selfing interactions may also partially explain the high proportion of empty seeds.…”
Section: Current Patterns Of Pollen Dispersal and Mating In The Gofukmentioning
confidence: 91%
“…Estimates of the inbreeding depression using the regression of fitness by selfing rate were mainly used for early life stages and particularly for seed production in forest trees (Burczyk et al 1991;Kormutak and Lindgren 1996;Wang 2003;Restoux 2009) but it could be applied to all estimates of fitness or all organisms with a mixed mating system such as herbaceous plants (Culley et al 1999;Weller et al 2005). The aim of this study is to investigate the factors that can reduce the detection power of inbreeding depression.…”
Section: Introductionmentioning
confidence: 99%